Design of an Infrared Imaging System for Robotic Inspection of Gas Leaks in Industrial Environments. (20th March 2015) - Barber, Ramon; Rodriguez-Conejo, Miguel A.; Melendez, Juan; Garrido, Santiago
Gas detection can become a critical task in dangerous environments that involve hazardous or contaminant gases, and the use of imaging sensors provides an important tool for leakage location. This paper presents a new design for remote sensing of gas leaks based on infrared (IR) imaging techniques. The inspection system uses an uncooled microbolometer detector, operating over a wide spectral bandwidth, that features both low size and low power consumption. This equipment is boarded on a robotic platform, so that wide objects or areas can be scanned. The detection principle is based on the use of active imaging techniques, where the use of external IR illumination enhances the detection limit and allows the proposed system to operate in most cases independently from environmental conditions, unlike passive commercial approaches. To illustrate this concept, a fully radiometric description of the detection problem has been developed; CO2 detection has been demonstrated; and simulations of typical gas detection scenarios have been performed, showing that typical industrial leaks of CH4 are well within the detection limits. The mobile platform where the gas sensing system is going to be implemented is a robot called TurtleBot. The control of the mobile base and of the inspection device is integrated in ROS architecture. The exploration system is based on the technique of Simultaneous Localization and Mapping (SLAM) that makes it possible to locate the gas leak in the map.